Translation of the Youth Attitude to Noise Scale and evaluation of Samoan university student attitudes towards recreational and environmental noise: A cross-sectional study to support the development of noise health promotion strategies - Annette Kaspar; Rossana Tofaeono-Pifeleti; Galumalemana Hunkin; Lineta Tamanikaiyaroi; Carlie Driscoll; Sione Pifeleti (SAGE Open Medicine)
Objectives: According to the World Health Organisation, nearly 50% of people aged 12–35 years worldwide are at risk of permanent hearing loss due to excessive and prolonged recreational and environmental noise exposure. There is no research literature on noise-induced hearing loss in the Pacific Islands. This study was conducted in order to support the development of public health policies and health promotion campaigns aimed at addressing preventable hearing loss among youth and young adults in Samoa. Methods: The Youth Attitude to Noise Scale is a validated 19-item questionnaire requiring a response on the 5-point Likert scale. The Youth Attitude to Noise Scale was formally translated into Samoan, and a bilingual version (English/Samoan) was administered to university students in Samoa to assess their attitudes towards recreational and environmental noise. Participants ( N  = 129, 39.5% male, 38% female, 22.5% missing data) represented the School of Medicine ( N  = 24), the Center for Samoan Studies ( N  = 29), and the Faculty of Technical Education ( N  = 76). Age range was 15–30 years (mean = 19.54, median = 19.00, SD = 2.9). Results: A total of 61.2% of participants agreed that there should be more rules/regulations for the sound levels in society, with more female students agreeing with this statement than male; 46.6% felt entertainment venues were too loud, with more medical students supporting this statement than either technical education or Samoan Studies students. A total of 72.9% agreed it should be quiet in classrooms; 60.5% were prepared to help make the educational environments quieter; 58.9% responded that listening to music helps them concentrate when doing homework; and 45.7% responded that it was difficult to concentrate when surrounded by many different sounds. Conclusion: Results indicated that there was a readiness among young adults to participate in the co-design of noise health policies, including the development of noise health promotion campaigns.